Agrarian technology in the medieval landscape Ruralia X, 9th-15th September 2013, Smolenice Castle, Slovakia = Agrartechnik in mittelalterlichen Landschaften = Technologie agraire dans le paysage médiéval - Klápště, Jan 1949- (Brepols, 2016)
The 'Ruralia', Volume 10, includes 27 papers dealing with agrarian technologies in the medieval landscape as seen in different European countries. The subject areas included cultivation, livestock husbandry, gardening, viticulture and woodland management - interpreting the concept of agrarian production in a broad sense - studied mainly on the basis of archaeology, but also using iconography, documentary evidence and archaeo-environmental approaches. The 'Ruralia', Volume 10, marks an important step on the way towards interpreting innovation, as well as understanding the varieties of agrarian activity from a Europe-wide perspective. The authors from 14 countries provide a broad overview of the current issues, complemented by extensive bibliographies. The 'Ruralia', Volume 10, represents one of the current fields of European archaeological research and offers a solid foundation for further comparative studies."--Back cover
Beiträge englisch, 2 Beiträge deutsch
Keywords: Geschichte 500-1500; Agriculture / Europe / History / To 1500 / Congresses; Land use, Rural / Europe / History / To 1500 / Congresses; Landscapes / Europe / History / To 1500 / Congresses; Archaeology, Medieval / Europe / Congresses; Geschichte; Landwirtschaft; Europa; Konferenzschrift; Konferenzschrift -- 2013 -- Smolenice